Avaliação de características de ordenhabilidade e comportamento de vacas ordenhadas em sistemas robotizados - Rodriguez, Flor Ángela Niño (2020)
The objective was to analyze some milkability and behavior traits of dairy cows in robotic milking systems with guided traffic like feed first and milk first from different genetic groups and and calving orders, as well as analyzing the correlations between these traits. The data for the period from September 2019 to March 2020, from two commercial dairy herds located in the State of Minas Gerais. Daily records of milkability traits as average flow rate (FR), box time (BT) and milking efficiency (ME); as well as behavior traits: handling time (HT), incomplete milkings (IM) and kick-offs (KO). In addition to these variables, other data obtained from the milking system were analyzed, such as milking time (MT), frequency (MF) and milking interval (MI). The averages of these in relation to genetic group and calving orders were compared. ANOVA analysis of variance was used, with analysis of univariate differences by the T test; and for multivariate comparisons, the Tukey test was used. In the herd using the feed first system, the multiparous cows in the two genetic groups showed more favorable characteristics compared with the primiparous cows (FR, BT, ME, HT, P < 0.01); ); except for Holstein x Jersey crossbred, with regard to KO, IM and MF. The IM showed a greater relationship in terms of reduced milk production by 16% in Holstein breed cows and 17,8% in Holstein x Jersey crossbred cows (P < 0.01). KO reduced milk production by milking by 3.5% in Holstein cows, whereas in Holstein x Jersey crossbred cows they did not affect milk production. Holstein x Jersey crossbred cows, as well as multiparous cows, showed more favorable milkability and behavior traits. The values of HT behavior traits were better in primiparous cows. Primiparous cows had higher amounts of KO and multiparous cows, higher IM. The IM showed a greater relationship in terms of reduced milk production by 26.6% in primiparous cows and 26.7% in multiparous cows. KO decreased milk production by milking in 3.2% in primiparous cows, while in multiparous cows it decreased 2.0%. As for the correlations, considering the combined data from the two herds, they were moderate negatives between FR and BT; ME and HT; as well as BT and ME; and positive and high between FR and ME. Positive and high correlations were found between BT and HT; positive and moderate between ME and milk yield (MY); and low positive correlation between HT and KO. There was no correlation between milking frequency (MF) with KO and IM.